Rancang Bangun Sistem Absensi Guru Berbasis QR Code Untuk Monitoring Kehadiran Dan Aktivitas Mengajar Di SMKN 12 Kabupaten Tangerang - Wahyu Muhamad Satrio; Aldi Juli Wahyudi; Ahmad Fathur; Sadam Zulkliflar (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The development of information technology has encouraged educational institutions to implement digital systems to support school administration. One of the administrative activities requiring effective management is recording teacher attendance during teaching activities. Based on observations at SMKN 12 Kabupaten Tangerang, teacher teaching attendance was still recorded manually, making monitoring, recapitulation, and report generation inefficient. This community service activity aimed to design and implement a QR Code-based teacher attendance system to facilitate recording teacher attendance during each teaching session. The implementation method included partner needs identification, system design, web-based application development using PHP and MySQL, system implementation, and evaluation. The results showed that the system successfully recorded teaching activities digitally, provided faster attendance information, and generated automatic teaching attendance reports. The developed system improved the effectiveness, efficiency, and accuracy of monitoring teaching activities while supporting the digital transformation of school administration at SMKN 12 Kabupaten Tangerang.